Opportunities for passive cooling to mitigate the impact of climate change in Switzerland. (15th January 2022) - Silva, Ricardo; Eggimann, Sven; Fierz, Léonie; Fiorentini, Massimo; Orehounig, Kristina; Baldini, Luca
Abstract: Energy systems need to decarbonize rapidly whilst satisfying heating and cooling needs. In Switzerland, residential cooling has so far only a small impact on the national energy demand, but climate change and a larger uptake of cooling devices are expected to lead to future increases. This requires novel approaches for sustainable cooling solutions suitable for implementation at a national scale. Here, we explore the potential of night ventilation and window shading to reduce the buildings cooling demand in a changing climate. A physical bottom-up approach is used to simulate residential space cooling demand and to identify the passive cooling potential whilst considering a detailed representation of the Swiss building stock, featuring building age, construction properties, regional climate, urban layout and occupant behaviour. A supervised building type classification approach is applied to enable up-scaling to the national level. Results show that in 2050, the residential Swiss building stock will require a national cooling demand of around 10.2 TWh for a Representative Concentration Pathway scenario 4.5. Under such future climatic conditions, we simulated a potential to reduce the total cooling demand by 84%, with both passive cooling solutions combined. Individually, window shading could reduce cooling demands by 71% and night ventilation by 38%. We found that newer buildings (built after 2000) already account for about 50% of the total current cooling energy demand. Results demonstrate that night ventilation and window shading have the potential to mitigate the impact of climate change in Switzerland and to improve the sustainability and resilience of residential cooling. Graphical abstract: Image 1 Highlights: 10.2 TWh cooling demand is simulated for Swiss residential sector by mid-century. Passive cooling measures have the potential to reduce future cooling demand by 84%. An extensive and comprehensive bottom-up methodology is applied for Switzerland. A morphological building classification for cooling energy is applied for upscaling. Peak cooling demand can roughly be halved by night ventilation and window shading.